Oficina para abordagem ao comportamento suicida: Implementação na atenção primária à saúde - Santos, Daniele Cristina Ribeiro dos [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Suicide is one of the top 10 causes of death in the world. Every 40 seconds, a person dies by suicide, so that it becomes a public health problem and a condition of compulsory notification. Most suicides can be prevented, just look at the large number of people who were in consultation in Primary Care during the period of one year before the fact. Thus, an early identification of suicide risk is one of the threat factors. The present study aims to propose and implement workshops with problems to approach the person in psychological distress with suicidal behavior for workers and managers of Primary Health Care services. A qualitativequantitative research was carried out through research of an action that, in turn, corresponds to a methodological and technical strategy that allows structuring a social investigation with greater versatility in the execution and execution of the resources used in the investigation. To organize the workshop - held in three meetings - choose the use of the Arch of Charles Maguerez. After transcribing the narratives and recordings of the workshop, the data were analyzed according to the methodological framework of Content Analysis, in the representative and thematic aspect of Bardin. The product was developed for a workshop on three meetings that offered an educational space, reflection on action and theoreticalpractical integration in professional practice. As a result, participants were selected who develop strategies to lead or assist a person in psychological distress with suicidal behavior, articulating teamwork and supporting the Health Care Network and the Intersectoral Network. The indicator of this possibility led the participants to have a criticism about biomedical logic centered on referral to a specialty. We concluded that the workshop meetings were important to promote the training and awareness of the participants. These attitudes are fundamental to qualify as skills of Primary Health Care professionals when assisting the user in psychological distress and suicidal behavior.

O suicídio é uma das 10 principais causas de morte no mundo. A cada 40 segundos, morre uma pessoa por suicídio, de modo que se tornou um problema de saúde pública e um agravo de notificação compulsória. A maior parte dos suicídios pode ser prevenida, basta observar o grande número de pessoas que esteve em consulta na Atenção Primária durante o prazo de um ano antes do fato. Assim, a identificação precoce do risco de suicídio é um dos fatores de prevenção. O presente estudo tem por objetivo propor e implementar oficinas problematizadoras sobre a abordagem à pessoa em sofrimento psíquico com comportamento suicida para os trabalhadores e gestores dos serviços da Atenção Primária à Saúde. Foi realizada uma pesquisa de natureza qualitativa-quantitativa conduzida por meio do referencial da pesquisa ação que, por sua vez, corresponde a uma estratégia metodológica e técnica que permite estruturar uma investigação social com maior versatilidade na elaboração e execução dos recursos utilizados na investigação. Para organização da oficina – realizada em três encontros – optou-se pela utilização do Arco de Charles Maguerez. Após a transcrição das narrativas e das gravações da oficina, os dados foram analisados segundo o referencial metodológico da Análise de Conteúdo, na vertente representacional e temática de Bardin. O produto desenvolvido foi a oficina constituída por três encontros que proporcionaram um espaço educativo, de reflexão da ação e integração teórico-prática no exercício profissional. Como resultado foram identificados que os participantes desenvolveram estratégias para conduzir o atendimento a pessoa em sofrimento psíquico com comportamento suicida, articulando trabalho em equipe e apoio da Rede de Atenção à Saúde e da Rede Intersetorial. O vislumbre dessa possibilidade levou os participantes a terem criticidade acerca da lógica biomédico centrada de encaminhamento para a especialidade. Conclui-se que os encontros da oficina foram importantes para promover formação e sensibilização dos participantes. Essas atitudes são fundamentais para qualificar as habilidades dos profissionais da Atenção Primária à Saúde quando do atendimento do usuário em sofrimento psíquico e comportamento suicida.
Workshop to approach suicidal behavior: Implementation in primary health care
Keywords: Suicide; Compulsory notification; Primary health care; Training of human resources in health; Suicídio; Tentativa de suicídio; Notificação compulsória; Atenção primária à saúde; Capacitação de recursos humanos em saúde